Impact of ocean acidification and warming on the productivity of a rock pool community. (May 2018) - Legrand, Erwann; Riera, Pascal; Bohner, Olivier; Coudret, Jérôme; Schlicklin, Ferdinand; Derrien, Marie; Martin, Sophie
Abstract: This study examined experimentally the combined effect of ocean acidification and warming on the productivity of rock pool multi-specific assemblages, composed of coralline algae, fleshy algae, and grazers. Natural rock pool communities experience high environmental fluctuations. This may confer physiological advantage to rock pool communities when facing predicted acidification and warming. The effect of ocean acidification and warming have been assessed at both individual and assemblage level to examine the importance of species interactions in the response of assemblages. We hypothesized that rock pool assemblages have physiological advantage when facing predicted ocean acidification and warming. Species exhibited species-specific responses to increased temperature and pCO2 . Increased temperature and pCO2 have no effect on assemblage photosynthesis, which was mostly influenced by fleshy algal primary production. The response of coralline algae to ocean acidification and warming depended on the season, which evidenced the importance of physiological adaptations to their environment in their response to climate change. We suggest that rock pool assemblages are relatively robust to changes in temperature and pCO2, in terms of primary production. Highlights: Fleshy algae drive the response of assemblages. The response of coralline algae to global change depend on the season. Rock pool assemblages are robust to ocean acidification and warming.